Bachelor of Education (Engineering) Program : The Open University of Malaysia Model - Kanesan, Muthusamy; Sharifah Rosfashida Syed Abd Latif; Wei, Wen Shyang; Rosli Hamir; Mansor Fadzil; Naidu, R. S (The Asian Society of Open and Distance Education, 2007)
This paper gives an overview of the design and development of Bachelor of Education (Civil / Electrical / Mechanical Engineering) programs for delivery through open and distance learning methodology at the Open University Malaysia. Research was carried out extensively prior to the design and development processes. These programs were tailor designed to train in- service teachers attached to the Ministry of Education, Malaysia, and they constitute an integral part of the Ministry’s plan to ensure that all technical teachers in Malaysian secondary schools possess tertiary education by the year 2010. This paper focuses on the curriculum development, the learning methodology, the laboratory requirements and planning, the courseware development, the e-learning delivery platform, and on the program quality assurance. Besides these, the academic calendar adopted for the program is also discussed since it has a strong influence on the design of the curriculum and on the duration of this program. The programs were designed and developed to introduce some uniqueness that will ensure academic accreditation and at the same time meet the needs of the intended target group. (Authors' abstract)